2015
DOI: 10.9738/intsurg-d-15-00071.1
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine Supplementation Reduces Short-Term Neutrophil-Lymphocyte Ratio in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: This study aims to investigate whether preoperative L-carnitine supplementation affects the neutrophil-to-lymphocyte ratio (NLR) in patients undergoing coronary artery bypass grafting surgery. The neutrophil-to-lymphocyte ratio is an inflammatory marker that has proven usefulness for predicting postoperative complications in coronary artery bypass surgery. A lot of studies concerning the role of L-carnitine in the immune system have been performed, contradictory results have been reported on its effects on abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…demonstrated that L-CN supplementation reduced serum CRP (a marker of systemic inflammation) and plasma fibrinogen (an inflammation-associated coagulation factor) in patients who underwent hemodialysis [34] and increased the total antioxidant capacity and decreased IL-6 and TNF-α, which were effective in decreasing inflammatory status [35]. However, L-CN reduces the accumulation of neutrophil protein kinase C receptor due to its inhibition [36], and supplementation with L-CN reduces the postoperative neutrophil-lymphocyte ratio in the short term [37]. In this study, L-CN was closely related to GBB in DVT, and L-CN was more correlated with leukocytes (neutrophils, lymphocytes, monocytes), and for the first time, we also found a positive correlation between GBB and APTT and TT.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that L-CN supplementation reduced serum CRP (a marker of systemic inflammation) and plasma fibrinogen (an inflammation-associated coagulation factor) in patients who underwent hemodialysis [34] and increased the total antioxidant capacity and decreased IL-6 and TNF-α, which were effective in decreasing inflammatory status [35]. However, L-CN reduces the accumulation of neutrophil protein kinase C receptor due to its inhibition [36], and supplementation with L-CN reduces the postoperative neutrophil-lymphocyte ratio in the short term [37]. In this study, L-CN was closely related to GBB in DVT, and L-CN was more correlated with leukocytes (neutrophils, lymphocytes, monocytes), and for the first time, we also found a positive correlation between GBB and APTT and TT.…”
Section: Discussionmentioning
confidence: 99%